2022
DOI: 10.3389/fgene.2022.821406
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Bovine Rumen Tissue in Three Developmental Stages

Abstract: Rumen development is a crucial physiological challenge for ruminants. However, the molecular mechanism regulating rumen development has not been clearly elucidated. In this study, we investigated genes involved in rumen development in 13 rumen tissues from three developmental stages (birth, youth, and adult) using RNA sequencing. We identified that 6,048 genes were differentially expressed among three developmental stages. Using weighted correlation network analysis, we found that 12 modules were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…In these heatmaps, the DEmRNAs expression patterns at 0 d were significantly different from those at the other four stages. These results coincide with those of others, which found that the gene expression patterns of rumen at birth were completely different from those in youth and adulthood in Simmental beef cattle ( 34 ). We also found that the DEmRNAs expression patterns at 20 d and 60 d were similar, as well as at 15 m and in adulthood in four stomachs.…”
Section: Discussionsupporting
confidence: 92%
“…In these heatmaps, the DEmRNAs expression patterns at 0 d were significantly different from those at the other four stages. These results coincide with those of others, which found that the gene expression patterns of rumen at birth were completely different from those in youth and adulthood in Simmental beef cattle ( 34 ). We also found that the DEmRNAs expression patterns at 20 d and 60 d were similar, as well as at 15 m and in adulthood in four stomachs.…”
Section: Discussionsupporting
confidence: 92%
“…There have been several reports on the relationship between rumen tissue gene expression and carcass traits. The transcriptome analysis of rumen tissue of Simmental cattle under different developmental stage revealed genes influencing carcass weight, stomach weight, marbling score, backfat thickness, ribeye area and lean meat weight [ 89 ]. It has become clear that host gene expression and epigenetic regulation could also influence the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…For each stage-specific module, GO enrichment and KEGG pathway analyses were conducted using DAVID ( , accessed on 20 May 2022) and KOBAS ( , accessed on 20 May 2022). GO terms and pathways with a p -value ≤ 0.05 were defined as significantly enriched [ 24 ]. Genes in each stage-specific module were calculated separately by STRING ( , accessed on 20 May 2022) and Metascape ( , accessed on 20 May 2022), obtained the protein–protein interaction (PPI) network and imported into Cytoscape (v3.8.2, , accessed on 20 May 2022) [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%